2019
DOI: 10.1177/0269881118822048
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrists’ reflections on a medication-free program for patients with psychosis

Abstract: Background: Based on a collective action from a number of Norwegian user organizations for mental health, the Norwegian government demanded the regional health authorities to establish a medication-free treatment option for patients with severe mental illnesses. This change in governmental health policy has several direct implications, including making antipsychotic medication to a greater extent optional for patients with active psychosis. Aims: The sim of this study was to investigate psychiatrists’ reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…This contradicts the views of MFT as representing the wish of only a minority of service users. 26 It also contradicts the view that service users already have a crucial impact on choice regarding medication. 26 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This contradicts the views of MFT as representing the wish of only a minority of service users. 26 It also contradicts the view that service users already have a crucial impact on choice regarding medication. 26 …”
Section: Discussionmentioning
confidence: 99%
“… 26 It also contradicts the view that service users already have a crucial impact on choice regarding medication. 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a recent UK qualitative study identified factors underpinning prescribing behaviour that include prescribers’ level of experience, varying levels of perceived personal responsibility for prescribing and associated risks, collaboration and compromise, patient involvement, and research evidence [10] . Notably, a Norwegian interview study examining psychiatrists’ views of medication-free treatment for psychosis reported substantial concern among prescribers that justifying treatment without antipsychotics lacked evidence [11] .…”
Section: Introductionmentioning
confidence: 99%